Green HRM and OCBE in the Banking Sector: An Empirical View - Ogalo, Habil Slade; Fatima, Seerat; Hasnain, Amna (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present study was to examine the relationship between green HRM and Organizational citizenship behavior to environment (OCBE). The study tested the impact of green recruitment, green training and green rewards on OCBE in the banking sector of Bahrain. The bootstrapping results on the hypothesized relationship confirmed significant relationship between green recruitment and OCBE. Accordingly, the study also found support for green training and OCBE followed by empirical significance for green rewards and OCBE relationship simultaneously. The study has conclusively confirmed the significance of green human resource management practices towards enhancing organizational citizenship behaviors for environment. The study has forwarded noteworthy results for implications and future studies.